2006
DOI: 10.3844/ajptsp.2006.21.25
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina protects against cadmium-induced hepatotoxicity in rats

Abstract: Cadmium (Cd) is an environmental and industrial cumulative pollutant that most affects many organs specially the liver. The protective effect of Spirulina, filamentous blue green algae, on Cd -induced oxidative stress and hepatotoxicity was evaluated in male rats. Oral administration of water extract of Spirulina for seven days followed by an acute toxic dose of Cd (3.5 mg kg b.wt. 1 ), reduced the hepatotoxicity and attenuated the Cd-induced oxidative stress. Spirulina treatment showed marked reduction in ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 22 publications
0
24
0
1
Order By: Relevance
“…Cadmium has a high tendency to settle in the proximal tubule of the nephron, leading to nephrotoxicity and progressive renal failure (Gonick, 2008) and this nephrotoxicity caused by cadmium is markedly high in occurrence among individuals exposed to the heavy metal industrially and/or through food as well as environmental pollution (Gonick, 2008). Several studies have reported hepatotoxicity associated with cadmium intoxication in (Amin et al 2006, Alhazzi, 2008, Tarasub et al 2008 Rajasekaran and Periasamy, 2012). Other biochemical effects of cadmium include displacement of redox-active metals, depletion of redox scavengers, inhibition of anti-oxidant enzymes, and inhibition of the electron transport chain resulting in mitochondrial damage (Thevenod 2009, Cuypers et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Cadmium has a high tendency to settle in the proximal tubule of the nephron, leading to nephrotoxicity and progressive renal failure (Gonick, 2008) and this nephrotoxicity caused by cadmium is markedly high in occurrence among individuals exposed to the heavy metal industrially and/or through food as well as environmental pollution (Gonick, 2008). Several studies have reported hepatotoxicity associated with cadmium intoxication in (Amin et al 2006, Alhazzi, 2008, Tarasub et al 2008 Rajasekaran and Periasamy, 2012). Other biochemical effects of cadmium include displacement of redox-active metals, depletion of redox scavengers, inhibition of anti-oxidant enzymes, and inhibition of the electron transport chain resulting in mitochondrial damage (Thevenod 2009, Cuypers et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It represents a broad spectrum of antioxidative, anticancer, anti‐inflammatory, antibacterial and antiviral abilities (Amin et al, ; Finamore et al, ; Gaurav, Preet, & Dua, ). Based on experimental studies it has been postulated that spirulina, by acting as a powerful FR scavenger and chelating agent, may protect the liver from various hepatotoxic agents, including Cd (Amin et al, ; Gaurav et al, ). Available data from the literature show that spirulina seems to be effective in the prophylaxis of Cd‐induced liver injury (Amin et al, ; Gaurav et al, ).…”
Section: Polyphenol‐rich Products In Protection and Treatment Of Cd‐imentioning
confidence: 99%
“…Based on experimental studies it has been postulated that spirulina, by acting as a powerful FR scavenger and chelating agent, may protect the liver from various hepatotoxic agents, including Cd (Amin et al, ; Gaurav et al, ). Available data from the literature show that spirulina seems to be effective in the prophylaxis of Cd‐induced liver injury (Amin et al, ; Gaurav et al, ). Moreover, this algae has been reported to be effective in protection from genotoxic and spermatotoxic action of this heavy metal (Aly, Kotb, & Hammad, ; Farag, Abd EL‐Aziz, Ali, & Ahmed, ).…”
Section: Polyphenol‐rich Products In Protection and Treatment Of Cd‐imentioning
confidence: 99%
See 2 more Smart Citations